Oral health status among fifteen years-old students in Maysan governorate\Iraq - Ahmed M Mughamis; Ahlam T Mohammed (College of Dentistry/ University of Baghdad, 2014)
Background: Dental caries and periodontal disease are the most common and widely spread diseases affecting humans at different ages. Aim of this study is the assessment of prevalence and severity of dental caries, gingivitis, oral hygiene and enamel anomalies in relation to gender and residency among 15 years old students in Maysan governorate -Iraq. Materials and methods: The total sample composed of 750 students (400 males and 350 females, 450 urban and 300 rural) selected randomly from different high schools in the Governorate. Diagnoses and recording dental caries was according to the criteria of WHO (1987), Plaque index of Silness and Loe (1964) was used for plaque assessment, Ramfjord index (1959) was applied for the assessment of calculus, gingival index of Loe and Silness (1963) was followed for recording gingival health condition and criteria of WHO (1997) to assess enamel anomalies. Results: Caries prevalence was found to be (92.53%) of the total sample. The DMFS value was higher among females compared to males with statistically high significant difference (P